Risk assessment of shrimp-derived probiotics on culture performance and environmental biosafety in shrimp larvae rearing system - Yu, Junqi; Wu, Chengjia; Dong, Pengsheng; Chen, Chen; Chen, Heng; Chen, Jinfei; Liu, Xiaoshuang; Wang, Ke; Wang, Kai; Zhang, Demin (Frontiers in Marine Science, 2025)
Indigenous probiotics are widely applied in Penaeus vannamei aquaculture due to their potential to enhance disease resistance and promote growth. However, their biological and environmental safety requires comprehensive evaluation, particularly during the larval stage. This study investigated the effects of shrimp derived Lactobacillus casei HD1 and Bacillus licheniformis WZ1 on larval growth performance, aquatic bacterial communities, potential pathogens, and antibiotic resistance genes (ARGs), by using illumina sequencing and quantitative PCR (qPCR), comparing probiotic-treated and control (CK) groups. Probiotic supplementation significantly improved survival rate, biomass, and individual weight, while reducing concentrations of NH4+-N, NO3−-N, and PO43−-P in rearing water. Compared to the control, α-diversity of the aquatic microbiota increased significantly, accompanied by elevated relative abundances of Bacteroidota, Bacillota, and Balneolota. The results of qPCR showed that no significant changes in abundance of ARGs and Lactobacillus in taxa were observed, whereas Bacillus was significantly enriched within probiotic-adding, compared to CK group. Notably, structural equation modeling (SEM) revealed that probiotics enhanced aquaculture performance through multiple pathways: indirectly by modulating aquatic microbial communities and directly by mitigating waterborne nutrients. These findings support the use of targeted indigenous probiotics as a sustainable strategy to balance productivity with environmental health, reduce reliance on antibiotics, overcome larval survival bottlenecks, and ensure ecological safety. Furthermore, the distinct impacts of different probiotics on microbial structure and host performance highlight the importance of strategic formulation in probiotic combinations for shrimp larval aquaculture.